Emerging roles of primary cilia in the pathogenesis of amyotrophic lateral sclerosis - Takahashi, Hisashi; Kasai, Takashi; Miyagawa-Hayashino, Aya; Ohara, Tomoyuki (Frontiers in Neuroscience, 2025)
Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disease primarily affecting motor neurons, for which effective disease-modifying therapies remain elusive. Primary cilia are solitary microtubule-based organelles critical for signal transduction and have recently been implicated in ALS pathogenesis. In this review, we provide a basic overview of the structure, dynamics, and functions of primary cilia, particularly in the brain. We highlight accumulating evidence from ALS models showing altered ciliary structure and function and explore how mutations in ALS-associated genes such as NEK1, C21orf2, and C9orf72 disrupt ciliogenesis and ciliary signaling. Moreover, we examine the interplays between primary cilia dysfunction and known ALS-related mechanisms, including loss of proteostasis, abnormal RNA metabolism, microtubule dysfunction, neuroinflammation, and mitochondrial dysfunction. Collectively, the evidence suggests a bidirectional relationship in which ciliary impairment and ALS pathomechanisms reinforce one another in a vicious cycle. We further discuss emerging therapeutic strategies targeting ciliary function, as well as the potential for primary cilia as novel clinical applications. Our review highlights primary cilia as a previously underappreciated yet potentially important component of ALS biology, offering novel insights into disease mechanisms and future therapeutic development.